Efficacy, immunogenicity and safety of vaccination in adult patients with autoimmune inflammatory rheumatic diseases: a systematic literature review for the 2019 update of EULAR recommendations. Issue 2 (9th September 2019) - Rondaan, Christien; Furer, Victoria; Heijstek, Marloes W; Agmon-Levin, Nancy; Bijl, Marc; Breedveld, Ferdinand C; D'Amelio, Raffaele; Dougados, Maxime; Kapetanovic, Meliha C; van Laar, Jacob M; Ladefoged de Thurah, Annette; Landewé, Robert; et al.
Abstract : Aim: To present a systematic literature review (SLR) on efficacy, immunogenicity and safety of vaccination in adult patients with autoimmune inflammatory rheumatic diseases (AIIRD), aiming to provide a basis for updating the EULAR evidence-based recommendations. Methods: An SLR was performed according to the standard operating procedures for EULAR-endorsed recommendations. Outcome was determined by efficacy, immunogenicity and safety of vaccination in adult patients with AIIRD, including those receiving immunomodulating therapy. Furthermore, a search was performed on the effect of vaccinating household members of patients with AIIRD on the occurrence of vaccine-preventable infections in patients and their household members (including newborns). The literature search was performed using Medline, Embase and the Cochrane Library (October 2009 to August 2018). Results: While most investigated vaccines were efficacious and/or immunogenic in patients with AIIRD, some were less efficacious than in healthy control subjects, and/or in patients receiving immunosuppressive agents. Adverse events of vaccination were generally mild and the rates were comparable to those in healthy persons. Vaccination did not seem to lead to an increase in activity of the underlying AIIRD, but insufficient power of most studies precluded arriving at definite conclusions. The number of studies investigating clinical efficacy of vaccination is still limited. No studies on the effect of vaccinating household members of patients with AIIRD were retrieved. Conclusion: Evidence on efficacy, immunogenicity and safety of vaccination in patients with AIIRD was systematically reviewed to provide a basis for updated recommendations.